المؤشرات الموضوعية لجودة الحياة الاجتماعية في مدينة الكوت - بدر، شريهان مازن; السعدون، عبدالجليل ضاري Alsaadoun, Abduljalil Dari (جامعة الكوفة - كلية التربية للبنات, 2021)
جودة الحياة هي مسمى ذاتي يشير إلى الرفاهية الاجتماعية للأفراد والبيئة التي يعيشون فيها، لذلك بالنسبة للفرد فهي مجموعة مطالب أو حاجات يسعى الفرد إلى إشباعها أو توفيرها وهو راضي عنها، وعندما يشبع الفرد حاجاته، تحل محلها حاجات أخرى، لذلك يختلف مفهوم جودة الحياة من فرد إلى آخر، ومن مجتمع إلى آخر، ومن وقت إلى آخر. إذ ترتبط المؤشرات الموضوعية والمؤشرات الذاتية ارتباطا وثيقا بجودة الحياة، وبالتالي فالجوانب الذاتية والجوانب الموضوعية أسلوبان متكاملان، ولا يمكن أن يتم الفصل بينهما أو استغناء أحدهما عن الآخر، فكلاهما يلعبان دورا مهما في جودة الحياة، كما إن لجودة الحياة جانبا إيجابيا يتضح من خلال المؤشرات الذاتية في الرضا عن الحياة، وجودة المعيشة، وتحقيق الأهداف، كما أوضحت الدراسات أن هنالك علاقة بين المستوى الاقتصادي وجودة الحياة من خلال اتساع قدرة الفرد على اختيار الأفضل. Quality of life is a subjective name that refers to the social well-being of individuals and the environment in which they live, so for the individual it is a group of demands or needs that the individual seeks to satisfy or provide while he is satisfied with it, and when the individual satisfies his needs, it is replaced by other needs, so the concept of quality of life differs from an individual To another, and from one society to another, and from time to time. Objective and subjective indicators are closely related to the quality of life, and therefore the subjective and objective aspects are two complementary methods, and neither can be separated or dispensed from one from the other, both of which play an important role in the quality Alive E, as the quality of life has a positive aspect that is evident through subjective indicators in life satisfaction, quality of life, and achievement of goals, as studies have shown that there is a relationship between the economic level and quality of life through the expansion of the individual's ability to choose the best.
Keywords: المدن -- الحياة الحضرية -- جودة الحياة الاجتماعية -- الرفاهية الاجتماعية -- المجتمع العراقي -- المدن العراقية -- مدينة الكوت